Gaya Kepemimpinan Transaksional dan Need for Achievement terhadap Kinerja Karyawan PDAM Kota Malang - Dwi Yulis Susanto (Universitas Islam Tribakti Lirboyo Kediri, 2018)
This study examines interconnection between transactional leadership and need for achevement to employee performance in PDAM Malang. This research was conducted in PDAM Malang City. The population of this study are employees of PDAM Malang City amounting to 372 employees. Quantitative research method using Likert scale and using multiple linear regression method. The number of samples of 190 employees from the population of 372 employees PDAM Malang City by using purposive random sampling technique. Based on the result of hypothesis test, first hypothesis rejected which is no effect on the performance of the employee, the second hypothesis is accepted, wherever the need for achievement shows positive and significant effect on the employee performance, and the last hypothesis is accepted, it is persue just as positive and significant influence simultaneously on employee performance. Based on the determination coefficient obtained Adjusted R Square value of 0.139 means that the influence of employee performance variables caused by transactional leadership style variables and need for achievement is 13.9 percent, while the big influence on employee performance variables caused by other factors is by 86.1 percent Keywords: Transactional Leadership Style, Need for achievement, Employee Performance.